Pengambilan Keputusan Alokasi Biaya Promosi Produk Jasa Speedy di Kota Ambon - D. Tumanan; M. Amba (Industrial Engineering Study Program, Pattimura University, 2012)
Frequently, decision making in company management is faced with multiobjectives and its contradiction where need to be minized in order to receip a maximum profit. Problem of promotion costs alocation of speedy services product in Ambon has a relation with an increasing sales volume policy (customer numbers) through many kind of promotion. It can, in a one side, raise company incomes, and at the other side, multiply promotion costs. The problem is formulated as a goal programming model to provide an optimal cost allocation decision. By running it in WinQSB software, we find number of allocation for each alternative: Rp. 35.005.000 (alternative I), Rp. 31.681.248 (alternative II), Rp. 28.357.504 (alternative III), while other costs are Rp. 48.850.000 (promotion material cost), Rp. 29.800.000 (merchandise cost), dan Rp. 6.000.000 (exhibition cost). The results also show 2.022 as the lowest customer number and 4.632 as the highes one.